Clinical characteristics and prescriptions associated with a 2-year course of rapid cycling and euthymia in bipolar disorder: a multicenter treatment survey for bipolar disorder in psychiatric clinics - Takano, Chikashi; Kato, Masaki; Adachi, Naoto; Kubota, Yukihisa; Azekawa, Takaharu; Ueda, Hitoshi; Edagawa, Kouji; Katsumoto, Eiichi; Goto, Eiichiro; Hongo, Seiji; Miki, Kazuhira; Tsuboi, Takashi; et al. (Frontiers in Psychiatry, 2023)
Objective: In patients with bipolar disorder (BD), rapid cycling (RC) presents a risk for a more severe illness, while euthymia (EUT) has a better prognosis. This study focused on the progression of RC and EUT, which are contrasting phenomenology, and aimed to clarify the influence of patient backgrounds and prescription patterns on these different progressions, using a large sample from the first and second iterations of a multicenter treatment survey for BD in psychiatric clinics (MUSUBI). Methods: In the cross-sectional study (MUSUBI), a questionnaire based on a retrospective medical record survey of consecutive BD cases (N = 2650) was distributed. The first survey was conducted in 2016, and the second one in 2017. The questionnaire collected information on patient backgrounds, current episodes, and clinical and prescribing characteristics. Results: In the first survey, 10.6% of the participants had RC and 3.6% had RC for two consecutive years, which correlated with BP I (Bipolar disorder type I), suicidal ideation, duration of illness, and the use of lithium carbonate and antipsychotic medications. Possible risk factors for switching to RC were comorbid developmental disorders and the prescription of anxiolytics and sleep medication. Moreover, 16.4% of the participants presented EUT in the first survey, and 11.0% presented EUT for two consecutive years. Possible factors for achieving EUT included older age; employment; fewer psychotic symptoms and comorbid personality disorders; fewer antidepressants, antipsychotics, and anxiolytics, and more lithium prescriptions. Conclusion: RC and EUT generally exhibit conflicting characteristics, and the conflicting social backgrounds and factors contributing to their outcomes were distinctive. Understanding these clinical characteristics may be helpful in clinical practice for management of patients with BD.